PWE-199 Diagnostic Radiation Exposure in Patients with Crohn'S Disease Treated with Infliximab. (4th June 2013) - Ching, H-L; Pandey, R; Chariah, F; Lipman, G; Train, M; Mann, S
Abstract : Introduction: Exposure to radiation from diagnostic imaging is thought to be associated with an increase in cancer risk. Patients with Crohn's Disease (CD) frequently require x-ray exposure throughout the course of their illness. Studies have quantified cumulative radiation exposure in patients with CD 1 . However, as far as we know, there has only been one study that has identified infliximab as an independent risk factor for increased radiation exposure 2 . We aimed to quantify all imaging and associated radiation exposure for this subset of patients in our institution. Methods: Our unit is in a district hospital serving a population of 500, 000 across 2 sites. All patients with CD who have received infliximab from January 1997 to January 2013 were identified from our hospital databases. Diagnostic imaging records were also retrieved from the databases. Using local protocols, a mean effective dose for each imaging modality was calculated. The cumulative effective dose (CED) per patient was calculated as the sum of the mean effective dose for all imaging modalities. The mean diagnostic radiation exposure per year = CED/years of follow-up. Results: 131 patients (52% female, mean age 46 years) were included in the study. Total number of imaging procedures was 624 (plain abdominal film = 351, CT abdomen/pelvis = 168, barium study = 105). Other imaging modalities included MRI abdomen/pelvis = 72 and abdominal ultrasound = 65. Average total number of imaging per patient was 5 (plain abdominal film = 3, CT abdomen/pelvis = 1, barium study = 1). The total CED for all imaging was 1828.1 mSv (85% attributed to CT imaging). The mean CED per patient was 14.0mSv (range 0–171.9mSv) with the mean diagnostic radiation exposure per year being 2.4mSv/year (range 0–28.7mSv/year). Conclusion: Imaging requests in patients with CD is high, particularly when they have received infliximab. In spite of concerns about radiation risk, 93% of our patients have CED less than 50mSv exposure, a level considered to be associated with a low cancer risk. However, most patients are young and are likely to accumulate more radiation exposure over time. The move towards more specialised care should lead to reduction in use of CT scans and increased use of MRI and ultrasound studies. Disclosure of Interest: None Declared. Reference: Peloquin JM, et al. Diagnostic ionising radiation exposure in a population-based cohort of patients with inflammatory bowel disease. Am J Gastro 2008; 103:2015–22 2. Desmond AN, et al. Crohn's disease: factors associated with exposure to high levels of diagnostic radiation. Gut 2008; 57:1524–1529